The long shadow of Ferguson: legitimacy, legal cynicism, and public perceptions of police militarization - Moule, Richard K. (Crime & delinquency, 2019)
This study examines public perceptions of police militarization, specifically whether individuals believe police are too militarized, and support for practices associated with militarization. Drawing on concepts found in the legal socialization literature—legitimacy and legal cynicism—this study tests hypotheses regarding whether these constructs influence perceptions of militarization. Using a national sample of 702 American adults, a series of ordinary least squares regression models are used to analyze the relationships between legitimacy, cynicism, and perceptions of police militarization. Results suggested that higher levels of legitimacy reduced beliefs that police are too militarized while also increasing support for practices associated with militarization. Cynicism increased beliefs that the police are too militarized, but had no effect on support for militarization. Perceptions of militarization are thus influenced by legal socialization.